2021
DOI: 10.1609/aaai.v35i1.16157
|View full text |Cite
|
Sign up to set email alerts
|

Towards Balanced Defect Prediction with Better Information Propagation

Abstract: Defect prediction, the task of predicting the presence of defects in source code artifacts, has broad application in software development. Defect prediction faces two major challenges, label scarcity, where only a small percentage of code artifacts are labeled, and data imbalance, where the majority of labeled artifacts are non-defective. Moreover, current defect prediction methods ignore the impact of information propagation among code artifacts and this negligence leads to performance degradation. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…F. Yang et al [34] proposed a software defect prediction at the level of method call sequences, while Thomas Shippey et al [35] proposed a semi-supervised model named DPCAG for the defect prediction task. From the previous literature review, it is found that ELFF method-level datasets were not used in predicting within-project software defects based on the ELFF datasets bug related metrics, nor were they used to investigate the impact of ensemble learning techniques on the severe imbalance in the dataset.…”
Section: Research Gaps and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…F. Yang et al [34] proposed a software defect prediction at the level of method call sequences, while Thomas Shippey et al [35] proposed a semi-supervised model named DPCAG for the defect prediction task. From the previous literature review, it is found that ELFF method-level datasets were not used in predicting within-project software defects based on the ELFF datasets bug related metrics, nor were they used to investigate the impact of ensemble learning techniques on the severe imbalance in the dataset.…”
Section: Research Gaps and Contributionsmentioning
confidence: 99%
“…DEVELOPING A METHOD FOR CLASSIFYING ELECTRO-OCULOGRAPHY (EOG) SIGNALS USING DEEP LEARNING 35 1. Investigating the use of ELFF method-level datasets to perform software defect prediction using ELFF software metrics.…”
Section: Research Gaps and Contributionsmentioning
confidence: 99%